2008
DOI: 10.1590/s0034-89102008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Factores salivales asociados a prevalencia e incremento de caries dental en escolares rurales

Abstract: OBJETIVO: Evaluar la asociación de la saliva y la prevalencia de caries. MÉTODOS: Estudio longitudinal de dos años, en una población de niños escolares rural de Cruz del Eje, Córdoba-Argentina, entre los años 2000 y 2002. La población de estudio comprendió la totalidad de escolares asistentes (N=196) a ocho escuelas rurales de 5 a 14 años de edad, ambos sexos. Se estudiaron tres momentos (N=46): base, 12 y 24 meses. Se evaluaron los componentes salivales y los índices CPOD y ceod. Se crearon las variables nomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
1
4
0
3
Order By: Relevance
“…The salivary alkaline phosphatase is one of the factors governing the calcium and phosphorous levels in saliva [29]. The mean salivary calcium and inorganic phosphorous levels in caries free group (Group-I) were higher as compared to caries active group (Group-II) and this difference was statistically not significant which are in accordance with the result of Gandhy and Damle [29], Marray and Shaw [30], Afshar et al [31], Cornejo et al [32], Masamurak et al [33]. These studies investigated the relationship between alkaline phosphatase and inorganic phosphorous with decayed, filled surface and observed that the level of alkaline phosphatase and inorganic phosphorous in rampant caries children was higher than the caries free children.…”
Section: Discussionsupporting
confidence: 70%
“…The salivary alkaline phosphatase is one of the factors governing the calcium and phosphorous levels in saliva [29]. The mean salivary calcium and inorganic phosphorous levels in caries free group (Group-I) were higher as compared to caries active group (Group-II) and this difference was statistically not significant which are in accordance with the result of Gandhy and Damle [29], Marray and Shaw [30], Afshar et al [31], Cornejo et al [32], Masamurak et al [33]. These studies investigated the relationship between alkaline phosphatase and inorganic phosphorous with decayed, filled surface and observed that the level of alkaline phosphatase and inorganic phosphorous in rampant caries children was higher than the caries free children.…”
Section: Discussionsupporting
confidence: 70%
“…In MPS patients a greater involvement of dentists is required, in order to arrive at better diagnostics and preventive protocols to improve oral health of these patients. 8,9,13,15,20,21,27,33,34 …”
Section: ■ Discussionmentioning
confidence: 99%
“…Abdullah et al showed that there is no significant difference between blood calcium concentration and blood thyroid hormone concentration which is in agreement with our results 24 . In the Cornejo study, caries in the molar teeth increased as salivary levels of calcium and phosphorus decreased 25 . Sewón et al showed that people with more salivary calcium had more caries‐free teeth and less DMFT 26,27 .…”
Section: Discussionmentioning
confidence: 99%